Tuberous Sclerosis: A Patient who presented with Fits - Noor Fatima, Noor Fatima; Madeeha Nazar, Madeeha Nazar; Muhammad Hamza, Muhammad Hamza; Sehrish Iqbal, Sehrish Iqbal; Nida Anjum, Nida Anjum; Muhammad Khurram, Muhammad Khurram; Faramarz Khan, Faramarz Khan (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Tuberous sclerosis is an autosomal dominant genetic disease that causes benign lesions in various organs such as the kidneys, heart, liver, eyes, lungs, and skin.1 The pathogenesis of this disease involves mutation of either gene TSC1 or gene TSC2, that code protein hamartin and tuberin respectively. These genes play an important role in suppression of tumor growth.2 Patients with tuberous sclerosis present with variety of symptoms that include seizures, intellectual disability, developmental delay, behavioral disorders, skin, lung and kidney lesions; it accounts to be the most common genetic cause of epilepsy.3 The diagnosis of tuberous sclerosis is made on the presence of major and minor criteria (detailed in table I) which are then analyzed to produce a definite or possible diagnosis. 1) Definite diagnosis: Two major features or one major feature with ≥2 minor features. 2) Possible diagnosis: Either one major feature or ≥2 minor features.4 Here we present a case of tuberous sclerosis who presented with fits.